Functionalities of the right and left hand in the context of handwriting expert opinion - Skubisz-Ślusarczyk, Sylwia; Zieniewicz, Iwona (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Undoubtedly, handwriting research contributes to broadening knowledge about the mechanism of development of handwriting ability. Most papers tend to discuss this issue on a global basis, taking into account graphisms of persons who are learning to write from first principles, although it should be noted that the sphere of handwriting examiners’ interest also covers more detailed issues, such as left-handedness. This problem has involved handwriting experts for years, and for that reason the objective of the present publication is to present, in an abbreviated form, the directions of experimental studies conducted on left-handed handwriting, and the results obtained in that field.
Keywords: ekspertyza pisma ręcznego; leworęczność; pismo praworęczne i leworęczne; cechy pisma ręcznego; ilość i jakość; identyfikacja